NEGOTIATING TRADITIONAL RELIGIOUS AUTHORITY IN INDONESIAN ISLAM : THE CASE OF MADANI VILLAGE - Rosidi, Imron; Saputra, Eko; Khotimah, Khotimah; Ganiyev, Avazbek; Masduki, Masduki; Ghofur, Abd. (Universitas Islam Negeri Ar-Raniry, 2024)
This article deals with traditional religious authority in a given context, namely the village of Madani in Riau, Sumatra, Indonesia. It specifically asks how this traditional religious authority is established and shaped in the context of an Indonesian rural Muslim society. This article uses observation and interviews to collect data based on an ethnographic study. This village is selected to be the place of study because it represents the typical characteristics of Indonesian villages. This article finds that traditional religious authority in Indonesia is not established and shaped linearly. However, it is compromised and contested. Although Muslims in this community regard a Kiai as a respected man having a religious charisma, this society also contests his religious authority to contribute to the resignation of the kiai from the Pesantren (Islamic Boarding School). This resignation supports him in developing his Tariqah (Sufi Order), followed by many community Muslims. Although he does not own a Pesantren, it indicates that his religious authority has been negotiated through the Tariqah. This negotiation implicates that traditional religious authority in Indonesia is not given without contestation from the Muslim community. Furthermore, it also indicates that traditional religious authority's trajectory and shape in rural areas are not monolithic, depending on society's social and cultural context.